Electrical reliability of different alloying content on copper alloy fillers in electrically conductive adhesives - Lin-Ngee, Ho; Teng, Fei Wu; Nishikawa, Hiroshi; Takemoto, Tadashi; Miyake, Koichi; Fujita, Masakazu; Ota, Koyu (Springer, 2011)
Link to publisher's homepage at http://www.springerlink.com/